Quality of Higher Education in Russia: Role of Competition and Job Market - Leonid Polischuk; Erik Livni (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
The paper analyzes the incentives faced by universities to provide high quality education services as they are shaped by competition and labor market signals. The paper argues that in higher education, unlike other sectors of the economy, liberalization and competition in and of themselves do not ensure quality. This conclusion holds for both the mass and elite segments of the university system. The authors further discuss alternative models of interaction between the labor market and the university system, as well as government policies and other means of correcting higher education market failures.